High fidelity progressive reinforcement learning for agile maneuvering UAVs - Bekar, Can; Yuksek, Burak; Inalhan, Gokhan (AIAA, 2020)
In this work, we present a high fidelity model based progressive reinforcement learning method for control system design for an agile maneuvering UAV. Our work relies on a simulation-based training and testing environment for doing software-in-the-loop (SIL), hardware-in-the-loop (HIL) and integrated flight testing within photo-realistic virtual reality (VR) environment. Through progressive learning with the high fidelity agent and environment models, the guidance and control policies build agile maneuvering based on fundamental control laws. First, we provide insight on development of high fidelity mathematical models using frequency domain system identification. These models are later used to design reinforcement learning based adaptive flight control laws allowing the vehicle to be controlled over a wide range of operating conditions covering model changes on operating conditions such as payload, voltage and damage to actuators and electronic speed controllers (ESCs). We later design outer flight guidance and control laws. Our current work and progress is summarized in this work.